Task-based Search: A Search Engine Perspective - Dumais, Susan (2013)
Identifying tasks using implicit interactions. This is especially important for tasks that extend across time and devices. The references below provide examples of techniques for identifying queries related to tasks, for predicting whether a task will be resumed, and looking at tasks over a longer time scale. References Alexander Kotov, Paul N. Bennett, Ryen W. White, Susan T. Dumais, and Jaime Teevan. Modeling and analysis of cross-session search tasks. In Proceedings of the 4th International ACM SIGIR Conference on Research and Development in Information Retrieval, SIGIR '11, pages 5–14, New York, NY, USA, 2011. ACM. Debora Donato, Francesco Bonchi, Tom Chi, and Yoelle Maarek. Do you want to take notes?: identifying research missions in yahoo! search pad. In Proceedings of the 19th International Conference on World Wide Web, WWW '10, pages 321–330, New York, NY, USA, 2010. ACM. Thinking broadly about what support for search tasks looks like. The references below provide examples from simple "answers" seen in web search engines, to apps for specific tasks, to richer environments for exploratory search. References Lydia B. Chilton and Jaime Teevan. Addressing people's information needs directly in a web search result page. In Proceedings of the 20th International Conference on World Wide Web, WWW '11, pages 27–36, New York, NY, USA, 2011. ACM. 50 ultimate travel apps ... so far
Invited Talk at NSF Task-Based Information Search Systems Workshop